Alkali metal influences in aluminyl complexes - Grams, Samuel; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Dalton Transactions, 2022)
The previously reported potassium aluminyl complex [(BDI-H)Al−K+]2 was converted in Li+ or Na+ salts by a salt metathesis reaction with Li(BPh4) or Na(BPh4), respectively; BDI-H = dianionic [(DIPP)N-C(Me) 00000000 00000000 00000000 00000000 11111111 00000000 11111111 00000000 00000000 00000000 C(H)-C( CH2)-N(DIPP)2−] and DIPP = 2,6-diisopropylphenyl. The Rb and Cs aluminyl complexes were obtained by reaction of (BDI)Al with RbC8 or CsC8; BDI = HC[C(Me)N(DIPP)]2. Crystal structures of two monomers, (BDI-H)Al−Li+·(Et2O)2 and (BDI-H)Al−Na+·(Et2O)(TMEDA), and four dimers [(BDI-H)Al−M+]2 (M = Li, Na, Rb, Cs) are discussed. Lewis base-free dimers [(BDI-H)Al−M+]2 crystallize either as slipped dimers (Li+, Na+) in which each Al center features only one Al-M contact or as a symmetric dimer (K+, Rb+, Cs+) in which the cation bridges both Al centers. The dimer with the largest cation (Cs+) shows Cs⋯CH2 C interactions between dimers, resulting in a coordination polymer. AIM and charge analysis reveal highly ionic Al-M bonds with strong polarization of the Al lone-pair towards the smaller cation Li+ and Na+. The Al-M bonds become weaker from Li to Cs. Calculated dimerization energies suggest that in apolar solvents only complexes with the heavier metals Rb and Cs may be in a monomer-dimer equilibrium. This is confirmed by DOSY measurements in benzene. Dimeric aluminyl complexes with heavier alkali metals (K-Cs) react with benzene to give a double C-H activation in para-positions.
CRIS-Team Scopus Importer:2022-08-12

Boosting Low-Valent Aluminum(I) Reactivity with a Potassium Reagent - Grams, Samuel; Eyselein, Jonathan; Langer, Jens; Färber, Christian; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
The reagent RK [R=CH(SiMe3)2 or N(SiMe3)2] was expected to react with the low-valent (DIPPBDI)Al (DIPPBDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-iPr-phenyl) to give [(DIPPBDI)AlR]−K+. However, deprotonation of the Me group in the ligand backbone was observed and [H2C=C(N-DIPP)−C(H)=C(Me)−N−DIPP]Al−K+ (1) crystallized as a bright-yellow product (73 %). Like most anionic AlI complexes, 1 forms a dimer in which formally negatively charged Al centers are bridged by K+ ions, showing strong K+⋅⋅⋅DIPP interactions. The rather short Al–K bonds [3.499(1)–3.588(1) Å] indicate tight bonding of the dimer. According to DOSY NMR analysis, 1 is dimeric in C6H6 and monomeric in THF, but slowly reacts with both solvents. In reaction with C6H6, two C−H bond activations are observed and a product with a para-phenylene moiety was exclusively isolated. DFT calculations confirm that the Al center in 1 is more reactive than that in (DIPPBDI)Al. Calculations show that both AlI and K+ work in concert and determines the reactivity of 1.
CRIS-Team Scopus Importer:2020-07-10
Keywords: aluminum; C−H activation; density-functional calculations; low-valent complexes; potassium

Calcium-Catalyzed Arene C-H Bond Activation by Low-Valent Al-I - Brand, Steffen; Elsen, Holger; Langer, Jens; Grams, Samuel; Harder, Sjoerd (Angewandte Chemie International Edition, 2019)
The low-valent ss-diketiminate complex ((BDI)-B-DIPP)Al is stable in benzene but addition of catalytic quantities of [((BDI)-B-DIPP)CaH](2) at 20 degrees C led to ((BDI)-B-DIPP)Al(Ph)H ((BDI)-B-DIPP=CH[C(CH3)N-DIPP](2), DIPP=2,6-diisopropylphenyl). Similar Ca-catalyzed C-H bond activation is demonstrated for toluene or p-xylene. For toluene a remarkable selectivity for meta-functionalization has been observed. Reaction of ((BDI)-B-DIPP)Al(m-tolyl)H with I-2 gave m-tolyl iodide, H-2 and ((BDI)-B-DIPP)AlI2 which was recycled to ((BDI)-B-DIPP)Al. Attempts to catalyze this reaction with Mg or Zn hydride catalysts failed. Instead, the highly stable complexes ((BDI)-B-DIPP)Al(H)M((BDI)-B-DIPP) (M=Mg, Zn) were formed. DFT calculations on the Ca hydride catalyzed arene alumination suggest that a similar but more loosely bound complex is formed: ((BDI)-B-DIPP)Al(H)Ca((BDI)-B-DIPP). This is in equilibrium with the hydride bridged complex ((BDI)-B-DIPP)Al(mu-H)Ca((BDI)-B-DIPP) which shows strongly increased electron density at Al. The combination of Ca-arene bonding and a highly nucleophilic Al center are key to facile C-H bond activation.
CRIS-Team WoS Importer:2019-10-01

Dipyrromethene and beta-Diketinninate Zinc Hydride Complexes: Resemblances and Differences - Ballmann, Gerd; Grams, Samuel; Elsen, Holger; Harder, Sjoerd (Organometallics, 2019)
A new dipyrromethene (DPM) ligand with bulky DIPP-substituents is introduced (DIPP = 2,6-diisopropylphenyl). The ligand, abbreviated as (DPM)-D-DIPP, was deprotonated with ZnEt2 to give ((DPM)-D-DIPP)ZnEt, which reacted with I-2 to form ((DPM)-D-DIPP)ZnI. Reaction of the latter with K[N(Pr-i)HBH3] afforded a labile Zn amidoborane complex which, after beta-hydride elimination, formed ((DPM)-D-DIPP)ZnH. Crystal structures of ((DPM)-D-DIPP)ZnX (X = Et, I, H) revealed their monomeric nature. The Zn-N bond distances are somewhat longer than those in the corresponding, monomeric beta-diketiminate complexes ((BDI)-B-DIPP)ZnX ((BDI)-B-DIPP = CH[C(Me)N-DIPP](2)). This is in agreement with calculated NPA charges, which are lower on the N atoms of DPM compared to those on BDI. Reaction of ((DPM)-D-DIPP)ZnH with CO2 gave ((DPM)-D-DIPP)Zn(O2CH), which crystallized as a monomer with a symmetrically bound eta(2)-formate ligand. In contrast, the beta-diketiminate complex crystallizes as a dimer [((BDI)-B-DIPP)Zn(O2CH)](2) with bridging formate ligands. Reaction of ((DPM)-D-DIPP)Zn(O2CH) with various silanes regenerated the hydride complex ((DPM)-D-DIPP)ZnH. Catalytic CO2 hydrosilylation with (EtO)(3)SiH using ((DPM)-D-DIPP)ZnH as a catalyst gave full reduction to [Si]-OMe species, whereas the catalyst ((BDI)-B-DIPP)ZnH only partially reduced CO2 to [Si]-OC(O)H. The advantage of the (DPM)-D-DIPP ligand is the arrangement of the DIPP-substituents, which form a pocket around the Zn-X unit, preventing dimerization and influencing its reactivity. In addition, in contrast to the negatively charged central backbone carbon in the (BDI)-B-DIPP ligand, that in (DPM)-D-DIPP is neutral. This makes it less nucleophilic and Bronsted basic, as expected for a true spectator ligand.
CRIS-Team WoS Importer:2019-08-09

Diverse Reactivity of a Ca(I) Synthon - Mai, Jonathan; Rösch, Bastian; Langer, Jens; Grams, Samuel; Morasch, Michael; Harder, Sjoerd (European Journal of Inorganic Chemistry, 2023)
Low-valent MgI complexes like (BDI)Mg−Mg(BDI) have found wide-spread application as specialty reducing agents (BDI=β-diketiminate). Also their redox reactivity was extensively investigated. In contrast, attempts to isolate similar CaI complexes led to reduction of the aromatic solvents or N2. Complex (DIPePBDI)Ca(μ6,μ6-C6H6)Ca(DIPePBDI) (VIII) should be regarded a CaII complex with a bridging C6H62− dianion (DIPePBDI=HC[C(Me)N-DIPeP]2, DIPeP=2,6-C(H)Et2-phenyl). It can react as a CaI synthon by releasing benzene and two electrons. Herein we describe the reactivity of VIII with benzene, biphenyl, naphthalene, anthracene, COT, Ph3SiCl, PhSiH3, a (BDI)AlI2 complex, H2, PhX (X=F, Cl, Br, I), tBuOH and tBuCH2I. The C6H62− dianion in VIII can react as a 2e− source, a nucleophile or a Brønsted base. In some cases radical reactivity cannot be excluded. Crystal structures of (DIPePBDI)Ca(μ8,μ8-COT)Ca(DIPePBDI) (1) and [(DIPePBDI)CaX ⋅ (THF)]2 (X=F, Cl, Br, I) (2–5) are described.
CRIS-Team Scopus Importer:2023-09-15
Keywords: Calcium; low-valent compounds; reactivity; reduction; β-diketiminate

Formation and Reactivity of Non-Stabilized Monomeric Alumoxane Intermediates - Grams, Samuel; Maurer, Johannes; Patel, Neha; Langer, Jens; Harder, Sjoerd (Zeitschrift für Anorganische und Allgemeine Chemie, 2022)
Several methods for the oxidation of the β-diketiminate AlI complexes (BDI)Al and (BDI*)Al with O2, Et3P=O or N2O are presented (BDI=HC[C(Me)N(DIPP)]2, DIPP=2,6-diisopropylphenyl; BDI*=HC[C(tBu)N(DIPP)]2). The selectivity of alumoxane formation depends strongly on the nature of the β-diketiminate ligand, the experimental procedure and the solvent. The mononuclear alumoxanes (BDI)Al=O and (BDI*)Al=O are highly reactive intermediates that cannot be isolated but either aggregate to give less reactive dimers or decompose by internal C−H activation of a backbone Me group or an iPr group. Ethereal solvents like Et2O react with alumoxanes to give (BDI)Al(OEt)OH and ethylene by β-H elimination. In case of N2O oxidation, subsequent reaction with a second equivalent of N2O to form the hyponitrite complexes (BDI)Al(N2O2) and (BDI*)Al(N2O2) is observed. Details of the alumoxane formation, reactivity and decomposition have been obtained by DFT calculations. These calculations also underscore their rather bipolar character, represented by the resonance structure (BDI)Al+−O−, and estimate the σ- and π-bond character of the Al=O bond at circa 76 % and 24 %, respectively.
CRIS-Team Scopus Importer:2022-03-11
Keywords: Aluminium; Alumoxane; DFT calculations; Low-valent; β-diketiminate

Highly Active Superbulky Alkaline Earth Metal Amide Catalysts for Hydrogenation of Challenging Alkenes and Aromatic Rings - Martin, Johannes; Knüpfer, Christian; Eyselein, Jonathan; Färber, Christian; Grams, Samuel; Langer, Jens; Thum, Katharina; Wiesinger, Michael; Harder, Sjoerd (Angewandte Chemie International Edition, 2020)
Two series of bulky alkaline earth (Ae) metal amide complexes have been prepared: Ae[N(TRIP)2]2 (1-Ae) and Ae[N(TRIP)(DIPP)]2 (2-Ae) (Ae=Mg, Ca, Sr, Ba; TRIP=SiiPr3, DIPP=2,6-diisopropylphenyl). While monomeric 1-Ca was already known, the new complexes have been structurally characterized. Monomers 1-Ae are highly linear while the monomers 2-Ae are slightly bent. The bulkier amide complexes 1-Ae are by far the most active catalysts in alkene hydrogenation with activities increasing from Mg to Ba. Catalyst 1-Ba can reduce internal alkenes like cyclohexene or 3-hexene and highly challenging substrates like 1-Me-cyclohexene or tetraphenylethylene. It is also active in arene hydrogenation reducing anthracene and naphthalene (even when substituted with an alkyl) as well as biphenyl. Benzene could be reduced to cyclohexane but full conversion was not reached. The first step in catalytic hydrogenation is formation of an (amide)AeH species, which can form larger aggregates. Increasing the bulk of the amide ligand decreases aggregate size but it is unclear what the true catalyst(s) is (are). DFT calculations suggest that amide bulk also has a noticeable influence on the thermodynamics for formation of the (amide)AeH species. Complex 1-Ba is currently the most powerful Ae metal hydrogenation catalyst. Due to tremendously increased activities in comparison to those of previously reported catalysts, the substrate scope in hydrogenation catalysis could be extended to challenging multi-substituted unactivated alkenes and even to arenes among which benzene.
CRIS-Team Scopus Importer:2020-04-03
Keywords: Alkaline Earth Metals; Alkenes; Aromatic rings; DFT calculations; Hydrogenation

Hydrogen Isotope Exchange with Superbulky Alkaline Earth Metal Amide Catalysts - Martin, Johannes; Eyselein, Jonathan; Grams, Samuel; Harder, Sjoerd (ACS Catalysis, 2020)
Heavier alkaline earth (Ae) metal amide complexes hydrogen isotope exchange (HIE). The activities for D/H exchange Ae(NR2)(2) (Ae = Ca, Sr, Ba) were found to be highly active catalysts for between C6D6 and H-2 strongly increase with metal size (Ca < Sr < Ba) and with amide bulk: N(SiMe3)(2) < N(DIPP)(SiiPr(3))< N(SiiPr(3))(2), DIPP = 2,6-diisopropylphenyl. At 120 degrees C and pressures of 10-50 bar, no hydrogenation side-products are produced, and TONs of 205 and TOFs of 268, competitive with those for precious metal catalysts, have been achieved. The reverse H/D exchange between C6H6 and D-2 is even faster by a factor 1.5-2. Substrates also include a range of substituted arenes. Alkyl-substituted aromatic rings are preferably deuterated in acidic benzylic positions, and this tendency increases with the number of alkyl-substituents. Although unactivated (sp(3))C-H units could not be deuterated, the (sp(3))Si-H function in primary, secondary, and tertiary alkylsilanes could be converted. Two different pathways for C6H6/D-2 isotope exchange have been evaluated by DFT calculations: (A) a deprotonation/protonation mechanism and (B) direct nucleophilic aromatic substitution. Although the exact nature of the catalyst(s) is unclear, the first step is the conversion of Ae(NR2)(2) with D-2 into R(2)NAeD which can aggregate to larger clusters. Energy profiles with model catalysts (iPr(3)Si)(2)NAeD and [(Me3Si)(2)NAeD](2) (Ae = Ca or Ba) show that the direct nucleophilic aromatic substitution is the most likely mechanism for deuteration of arenes. The key to this unusual reaction is the initial formation of a pi-arene center dot center dot center dot Ae complex which is followed by the generation of an intermediate with a Meisenheimer anion. Heavier Ae metal amide complexes are, despite the lack of partially filled d-orbitals for substrate activation, potent catalysts for HIE.
CRIS-Team WoS Importer:2020-08-14

Synthesis, Structure, and Reactivity of a Superbulky Low-Valent β-Diketiminate Al(I) Complex - Grams, Samuel; Mai, Jonathan; Langer, Jens; Harder, Sjoerd (Organometallics, 2022)
Low-valent β-diketiminate Al(I) complexes are generally synthesized in low yields (<20%). This is due to an intermolecular decomposition reaction. A new β-diketiminate Al(I) complex with a very bulky β-diketiminate ligand DIPePBDI was obtained in a high yield (81%) and the raw product was found to be essentially pure (DIPePBDI = HC[C(Me)N(DIPeP)]2; DIPeP = 2,6-C(H)Et2-phenyl). The crystal structure of (DIPePBDI)Al shows a monomeric complex. The reaction of (DIPePBDI)Al with AlBr3 gave (DIPePBDI)AlBr2 and Al(0). The reaction of (DIPePBDI)Al with KCH(SiMe3)2 led to deprotonation of a backbone Me group and formation of a K aluminyl complex. A minor side-product in which the BDI ligand was cleaved is also described. The very high yield of (DIPePBDI)Al makes it a welcome addition to the family of β-diketiminate Al(I) complexes.
CRIS-Team Scopus Importer:2022-10-28